2023
DOI: 10.1007/s10147-023-02300-6
|View full text |Cite
|
Sign up to set email alerts
|

Health care professionals’ experiences of dealing with cancer cachexia

Abstract: Background Cancer cachexia (CC) is a debilitating syndrome severely impacting patients’ quality of life and survivorship. We aimed to investigate the health care professionals’ (HCPs’) experiences of dealing with CC. Methods Survey questions entailed definitions and guidelines, importance of CC management, clinician confidence and involvement, screening and assessment, interventions, psychosocial and food aspects. The online survey was disseminated through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 40 publications
(53 reference statements)
3
13
0
Order By: Relevance
“…16 Five major surveys evaluated cancer cachexia among global HCPs (Table S3). Four surveys focused on HCPs in medical oncology or palliative/supportive care, 9,10,18,19 while one targeted HCPs in general medicine. 11 In Australia and New Zealand, 36.3% of HCPs lacked confidence in managing cancer cachexia, 19 which aligns with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…16 Five major surveys evaluated cancer cachexia among global HCPs (Table S3). Four surveys focused on HCPs in medical oncology or palliative/supportive care, 9,10,18,19 while one targeted HCPs in general medicine. 11 In Australia and New Zealand, 36.3% of HCPs lacked confidence in managing cancer cachexia, 19 which aligns with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Four surveys focused on HCPs in medical oncology or palliative/supportive care, 9,10,18,19 while one targeted HCPs in general medicine. 11 In Australia and New Zealand, 36.3% of HCPs lacked confidence in managing cancer cachexia, 19 which aligns with our findings. Additionally, two studies 9,19 reported that 35-83% of HCPs misunderstood the weight loss cut-off.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations